NURSING CARE FOR INDIVIDUALS WITH LONG-TERM ILLNESSES - Thayibah Sayfi Almutairi, Wadha Marzouq ALbulaytih, Manar Saud Sarray Alanazi, Naif Noman Alshammari, Emad Faisal Shabander, Khaled Hamoud Alsofayany, Mona Malih alanazi,,; Amani Suwayyid Almutairi, Shuaa Mohammed Aldhafeeri, ‏Alanazi‏ Hamad Ghathith, Budur Obaid Aldhafeeri, Mona Obiad Aldhafeeri, Refah Nazal Aldafeeri, (Chelonian Research Foundation, 2022)
Context. Restoring and promoting self-management in individuals with chronic diseases or helping older adults maintain their independence are two strategies to improve health-related quality of life while potentially reducing costs. These kinds of interventions are frequently performed by nurses during follow-up home visits. Goals. to explain the effects of nursing interventions on individuals with a variety of chronic diseases during home visits. Approach. Using the databases from Medline, Embase, PsycINFO, CINAHL, and Cochrane as well as the terms chronic, diabetic, arthritis pain, and random, as well as [(nurses and care) or (nurse and interventions)], a systematic descriptive review was conducted. Results. The best results are obtained with older adults if "the younger-old" is the target population or if the intervention is specifically designed for older adults with known health issues. The length of the follow-up time, the quantity of follow-up visits, and the nurse's personality all affect the outcome. Patients with diabetes may benefit from follow-up nursing interventions that enhance their psychological and physical well-being. Keywords: result, educational background, nursing, long-term care, chronic illness, chronic condition, older adults